A NOVEL PHENYLALANINE AMMONIA-LYASE FROM KANGIELLA KOREENSIS - VARGA, Andrea; BATA, Zsófia; CSUKA, Pál; BORDEA, Diana Monica; VÉRTESSY, Beáta G.; MARCOVICI, Adriana; IRIMIE, Florin-Dan; POPPE, László; BENCZE, László Csaba (Studia Universitatis Babeș-Bolyai Chemia, 2017)
This study describes the cloning of the gene encoding a novel phenylalanine ammonia-lyase from Kangiella koreensis (KkPAL) into pET19b expression vector. Optimization of protein expression and purification conditions yielded 15 mg pure soluble protein from one liter of E. coli culture. Enzymatic activity measurements of the ammonia elimination reaction from different natural aromatic amino acids proved the protein to be a phenylalanine ammonia-lyase. The isolated protein showed remarkably high, 81.7 °C melting temperature, making it especially suitable for biocatalytic applications.